AFM-IR and IR-SNOM for the characterization of small molecule organic semiconductors - Rao, Vaishnavi J.; Matthiesen, Maik; Goetz, Katelyn; Huck, Christian; Yim, Chanyoung; Siris, Rita; Han, Jie; Hahn, Sebastian; Bunz, Uwe H. F.; Dreuw, Andreas; Duesberg, Georg S.; Pucci, Annemarie; et al. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
Vibrational spectroscopies, such as Raman and Fourier-transform infrared spectroscopy (FT-IR), are powerful tools for the characterization of organic semiconductor thin films and crystals in addition to X-ray diffraction and scanning atomic force microscopy. They enable the investigation of molecular orientation, polymorphism, doping levels, and intra- as well as intermolecular vibrational modes albeit without much spatial resolution. Two fundamentally different scanning probe techniques offer two-dimensional mapping of infrared-active modes with a spatial resolution below 100 nm: scattering-type scanning near-field optical microscopy (IR s-SNOM) and atomic force microscopy-infrared spectroscopy (AFM-IR). Here, we compare these two techniques with each other and to conventional FT-IR spectroscopy measurements with regard to their applicability to highly ordered molecular semiconductors. For this purpose, we use organic single crystals of rubrene, perfluorobutyldicyanoperylene carboxydiimide (PDIF-CN2), TIPS-pentacene, and TIPS-tetraazapentacene as model systems. We find significant spectral differences depending on the technique and polarization that are related to the anisotropy of the crystals and the fundamentally different working principles of the applied methods. The spatial and spectral resolution of IR s-SNOM and AFM-IR are further tested and compared for a polycrystalline thin film of PDIF-CN2.